Iris Recognition System With ID Fractal And Local Ordinal Measures Approaches - Teo, Chuan Chin (2007)
In this thesis, the basic characteristics of human iris are introduced. Some of the details acquired from the iris eye very useful to this project. Furthermore, some of the research works are reviewed for further investigation and comparison.. Overall, an automated iris recognition system is proposed in this thesis.